The Relationship Between the Attitude and Achievement in Mathematics for Intermediate Second Class Students - Awad, M. H (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Many studies mentioned that there is a decline in the a achievement of intermediate second class students in mathematics . Parents and mathematics teachers had emphasized that . The studies related this decline to the students weak attitude towards mathematics . In spite of the importance of this subject , it has not been given enough attention in research in our country . This research is an attempt to know th e relationships between the intermediate second class students , attitude and their achievement in mathematics . Also, to know the statistical sign ificance of this relationship according to the gender factor . To verify the research aims , a sample of ( 442) male and female st udents were chosen . The mean scores of their achievement in mathematics for the 1 51 semester of the academic year 2002-2003 were obtained from their schools . The students’ attitude was measured by a scale that was approved by experts . To analyze the data statistically , the researcher used number of statistical means . The results showed that :- 1- There is a weak relationship between the students attitude towards mathematics and their achievements . 2- The positive relationship between students, attitude and their achievement among male st udents is better than female students .